EDD 706: Educational Reforms Designed for Equity
This course examines the knowledge base of theories and grounded research that critique past and current educational reforms in the United States. Special attention will be paid to the theoretical frameworks that guided reforms, the work of professional practitioners, and the intended and unintended impacts on minoritized students, families, organizations, and communities. Knowledge acquired will be a basis for designing meaningful solutions to complex problems of practice that align theory and practice to focus on achieving social equity.